Left Atrial Isolation and Appendage Occlusion in Patients With Atrial Fibrillation at End-Stage Left Atrial Fibrotic Disease. (16th July 2021) - Zedda, Angela; Huo, Yan; Kronborg, Mads; Ulbrich, Stefan; Mayer, Julia; Pu, Liying; Richter, Utz; Gaspar, Thomas; Piorkowski, Judith; Piorkowski, Christopher
Abstract : Background: Atrial fibrillation (AF) ablation in an end-stage left atrial (LA) fibrotic disease is more complex, has more recurrences, and may compromise transport function and stroke risk. We explored whether a total left atrial isolation procedure (TLAI) followed by left atrial appendage occlusion is a feasible treatment concept for rhythm and stroke risk control. Methods: Patients with symptomatic AF with extended LA fibrosis were enrolled consecutively for TLAI followed by left atrial appendage occlusion. At enrollment, all patients received a sinus rhythm LA voltage map. For TLAI, LA anterior and paraseptal ablation lines were placed, combined with right atrial and epicardial line completion and right pulmonary vein isolation as needed. Rhythm follow-up was provided through continuous monitoring using implantable cardiac devices. Results: Ninety-two patients (71±9 years, 41% male, 84% persistent AF, CHA2 DS2 -VASc 4) underwent 104 ablation procedures. Follow-up duration measured 48±22 months. At 12-month follow-up 70 out of 92 (76%) patients were free from any atrial arrhythmia recurrence, off antiarrhythmic drugs. All intended left atrial appendage occlusion procedures were successfully performed 6 to 8 weeks after TLAI. Combination of TLAI and left atrial appendage occlusion attenuated the native 4% annual stroke risk to <1% over the entire course of the study. Patients' clinical AF and heart failure symptoms (European Heart Rhythm Association and New York Heart Association classification) significantly improved and remained stable during further follow-up. Invasive hemodynamic assessment as well as echocardiographic transport function analysis did not show evidence of detrimental hemodynamic effects of the treatment concept. Conclusions: This is the first report on a structured concept of interventional electrical LA isolation and LA appendage occlusion for rhythm and stroke risk control in patients with AF at an end-stage left atrial fibrotic disease. We report feasibility, safety, and efficacy of such a treatment approach.